The influence of RDI on competitiveness and specialisation of production and export in Europe - Dan Olteanu (Romanian Academy, National Institute for Economic Research, 2010)
This study analyses how the relative specialisation indexes of production and export for various categories of products are correlated with the technological level of a country expressed in RDI expenditures and number of patent applications to the EPO. We showed that the countries investing in research and achieve performance in innovation specialize in technology-intensive activities that benefit the national economy. Moreover, with regard to product differentiation (irrespective of industry), the countries produce and export high quality goods which embed significant RDI expenditures and human capital, benefiting from high export prices. Considering the classification of production by stages at production, their specialisation is achieved in goods having the highest value added, which also embed significant expenditures on RDI (components, accessories and capital goods).
Keywords: O33; C21; 330; RDI; competitiveness; technological specialisation